Effect of trypsin treatments on the structure and binding capacity of volatile compounds of myosin. (1st January 2017) - Lv, Tong; Wang, Ying; Pan, Daodong; Cao, Jinxuan; Zhang, Xin; Sun, Yangying; Chen, Yinji; Liu, Yuan
Highlights: Myosin with trypsin treatment produced LMM, S2, 100 and 65 kDa bands. Trypsin treatments unfolded the secondary structures of myosin. Trypsin treatments increased absorbing capacity of aldehydes and ketones. Trypsin treatments increased hydrophobicity and thiol groups. Abstract: In order to investigate the mechanism between flavor binding and proteins degradation during meat processing, the influence of different trypsin contents on the structure of myosin and the adsorption capacity on aldehydes and ketones was determined. The 1% treatment produced subfragment 2 (S2), light meromyosin (LMM) and decreased 18 and 16 kDa light chains; 5% and 10% treatments produced 100 and 65 kDa new bands and more S2, LMM and cleaned light chains. With the rising trypsin contents, β-sheet, β-turn, random coil, hydrophobicity and total sulfydryl content increased; solubility, α-helix and free percentages of aldehydes and ketones decreased. The increase of absorbing capacity could be attributed to the increased hydrophobicity and total sulphydryl and the unfolding of secondary structures by exposing reactive amino and thiol groups and hydrophobic sites; the decreased solubility was related to the increased hydrophobicity. The trypsin-dose dependent proteolysis of myosin increased the retention of volatile compounds.